Association of Personal Hygiene and Skin Disorders among Landfill Workers - Putri Maharani, Rakhel; Mashuri, Yusuf Ari; Sari, Yulia; Haryati, Sri (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Skin disorders are symptoms and signs that appear on the skin, such as redness, itching, bumps, cracked skin, and dry scaly skin caused by bacteria, viruses, fungi, parasitic infections, allergic reactions, and personal hygiene factors. Workers, including waste pickers and scavengers, often neglect their personal hygiene habits. The risk of skin disorders is also due to their activities that are always in contact with waste that accumulates in landfills. Purpose: This study aimed to determine the relationship between personal hygiene and skin disorders in workers at Putri Cempo landfill, Surakarta. Methods: An analytic observational study with a cross-sectional design using convenience sampling was conducted. The study included a total of 51 waste haulers and 22 scavengers. Personal hygiene data collection was carried out by filling out a questionnaire; kin disorder data was collected by analyzation of symptoms and direct observation of signs of skin disorders in workers. The Chi-Square test and Cramer's V test were used to assess the association. Result: The prevalence of skin disorders among workers at Putri Cempo landfill, Surakarta, was 46.6%. The predilections of skin disorders were on the hands, feet, and nails, with 31.5% itchy complaints and 17.8% dry and scaly skin. There was a significant relationship (p <0.001) with a moderately strong correlation (v = 0.431) between personal hygiene and skin disorders. Conclusion: Personal hygiene is significantly associated and moderately correlated with skin disorders in workers at Putri Cempo landfill, Surakarta. A comprehensive approach to tackle the problems are urgently needed.